2015
DOI: 10.5397/cise.2015.18.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration Exists along the Entire Length of the Supraspinatus Tendon in Patients with a Rotator Cuff Tear

Abstract: Background: The purposes of the study were to examine rotator cuff tendon degeneration with respect to harvesting location, to determine a rationale for debridement of the torn end, and thus, to determine adequate debridement extent. Methods: Twenty-four patients with a full-thickness rotator cuff tear were included in the study. Tendon specimens were harvested during arthroscopic rotator cuff repair from three locations; from torn ends after minimal regularization of fraying (native end group, NE group), from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In our study, however, no significant differences in tendon degeneration were found between patients with different-sized full-thickness rotator cuff tears. In several studies using the same histological grading system as that used in this study, the average total degeneration score for full-thickness tears ranged from 12 to 15 [ 24 , 25 ], suggesting that a total degeneration score of 12 or higher may indicate that tendon degeneration has already reached the end stages. The results of this study are consistent with those of previous studies [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, however, no significant differences in tendon degeneration were found between patients with different-sized full-thickness rotator cuff tears. In several studies using the same histological grading system as that used in this study, the average total degeneration score for full-thickness tears ranged from 12 to 15 [ 24 , 25 ], suggesting that a total degeneration score of 12 or higher may indicate that tendon degeneration has already reached the end stages. The results of this study are consistent with those of previous studies [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 96%
“…In several studies using the same histological grading system as that used in this study, the average total degeneration score for full-thickness tears ranged from 12 to 15 [ 24 , 25 ], suggesting that a total degeneration score of 12 or higher may indicate that tendon degeneration has already reached the end stages. The results of this study are consistent with those of previous studies [ 20 , 24 ]. Because a full-thickness rotator cuff tear is the final stage in the rotator cuff tear spectrum, it is possible that any degenerative changes in the torn tendons may already have progressed to the end stage, which is why no significant differences of tendon degeneration were found between the healed and retear groups.…”
Section: Discussionmentioning
confidence: 96%
“…Each slide was evaluated with a semi-quantitative grading scale of Aström and Movin modified by Maffulli. 6,17,18) The parameters included in the scale were fiber structure, fiber arrangement, rounding of nuclei, regional variations in cellularity, increased vascularity, decreased collagen stainability, and hyalinization. A 4-point scoring system was used; 0 indicates normal appearance, 1 slightly abnormal, 2 moderately abnormal, and 3 markedly abnormal.…”
Section: Tendon Harvesting and Histological Assessmentsmentioning
confidence: 99%
“…Whole area of each slide was observed, and the most severely degenerated area, possibly expecting the worst score, was selected and used in the study. 6) Examination was performed by a fellowship trained orthopedic surgeon and pathologist. Each slide was evaluated with a semi-quantitative grading scale of Aström and Movin modified by Maffulli.…”
Section: Tendon Harvesting and Histological Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation